Documentary Film Production Management of the Baduy Community Based on Audio Spatialization Using BandLab - Maghfira Izzani Maulania; Hudi Santoso (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The increasing need for innovative approaches in cultural preservation has encouraged the use of documentary films as effective media for communicating indigenous knowledge and traditions. This study aims to examine the production management of the cultural documentary film Belajar dari Tanah Adat Baduy and evaluate the implementation of audio spatialization techniques using BandLab in enhancing audience experience. Employing a qualitative approach, data were collected through observation, interviews, documentation, and literature review during the pre-production, production, and post-production stages conducted in Kanekes Village, Lebak Regency, Banten. Production management was analyzed using the POAC framework (Planning, Organizing, Actuating, and Controlling), while production performance was evaluated using the VRIO framework (Value, Rarity, Imitability, and Organization). The findings indicate that documentary production was characterized by dynamic managerial adjustments, including schedule changes, role overlap, and field adaptations resulting from technical limitations and cultural considerations. The application of audio spatialization through stereo panning manipulation in BandLab successfully enhanced the sense of spatial depth and immersion despite resource constraints. VRIO analysis demonstrates that the documentary possesses educational and cultural value, a distinctive audio-production approach, and effective resource organization, although its technical features remain relatively easy to replicate. The study concludes that accessible digital platforms such as BandLab can support innovative audio production in cultural documentary filmmaking while enabling effective management of limited resources in indigenous cultural documentation.